Effect of Er: YAG laser therapy in non-surgical periodontal treatment: an umbrella review - Khalid Gufran; Abdullah Saad Alqahtani; Mohammed Alasqah; Abdulaziz Alsakr; Hassan Alkharaan; Hanadi Ghurmallah Alzahrani; Abdullah Almutairi (BMC Oral Health)
Abstract Aim The current umbrella review aimed to summarize the effect of erbium-doped yttrium aluminum garnet (Er: YAG) laser adjunct with the conventional non-surgical periodontal treatment which was evidenced from available systematic reviews. Methods An extensive literature search was piloted by two independent reviewers in the PubMed, Scopus, Science Direct, and Google Scholar databases. The search was limited to the English language from 2011 to 2023 years. The methodological quality of systematic reviews 2 (AMSTAR 2) guideline was followed to evaluate the risk of bias for the selected studies. Cohen’s kappa statistic was implemented to evaluate the level of agreement to assess the risk of bias in the selected studies. Results A total of 472 studies were initially identified. After removing the duplicates and screening, a total of four studies were selected for the current overview. Based on the quality assessment tool, each study scored as high, moderate, low, and critically low-quality study following AMSTAR 2 tool. Inter-rater reliability by Cohen’s Kappa statistics showed near-perfect agreement (0.95) between the two reviewers. Conclusion Even though weak evidence of effectiveness was observed for Er: YAG laser application in non-surgical periodontal treatment, the clinical benefits are still lacking.